Offshore outsourcing: Consequences and challenges for America - Ulrik Bie (Danmarks Nationalbank, 2005)
This paper is meant to provide a general overview of the subject of offshore outsourcing in America. The debate over offshore outsourcing has been triggered by the increasing trade deficit and steep decline in manufacturing employment over the latest business cycle. Furthermore, as technological advances allow for service functions to relocate abroad, a larger segment of workers are now faced with international competition. Most studies find that the current level of offshore outsourcing of services is benign compared to the net job creation in America. Estimates show that in the longer run, as many as 14 million service jobs are in danger. In manufacturing, still more areas are being affected by foreign competition. The offshore outsourcing of jobs and functions increases productivity and has a tendency to increase demand for higherskilled labour. It also lowers prices particularly benefiting lower-income families. On an aggregate basis, it provides America with a net gain. However, there is a growing concern that offshore outsourcing does not only imply transitional costs as the economy undergoes structural change, but that it creates a permanent downwards pressure on wages for many groups in competition with cheaper labour overseas. This entails more focus on the needs for adult training and education. Free world trade remains a precondition for globalisation and the exploitation of international division of labour. At both federal and state level of government, there is a trend towards more protectionism. The Chinese peg to the dollar and the opening of overseas markets for American goods and services have taken centre-stage.
Keywords: 330; Outsourcing; Internationale Arbeitsteilung; Multinationales Unternehmen; Beschäftigungseffekt; Globalisierung